Plastrum testudinis Ameliorates Oxidative Stress in Nucleus Pulposus Cells via Downregulating the TNF-α Signaling Pathway - Peng Zhang; Jiahui He; Yanchi Gan; Qi Shang; Honglin Chen; Wenhua Zhao; Gengyang Shen; Xiaobing Jiang; Hui Ren (Pharmaceuticals, 2023)
Background Plastrum testudinis (PT), a widely used traditional Chinese medicine, exerts protective effects against bone diseases such as intervertebral disc degeneration (IDD). Despite its effectiveness, the molecular mechanisms underlying the effects of PT on IDD remain unclear. Methods In this study, we used a comprehensive strategy combining bioinformatic analysis with experimental verification to investigate the possible molecular mechanisms of PT against IDD. We retrieved targets for PT and IDD, and then used their overlapped targets for protein–protein interaction (PPI) analysis. In addition, we used Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses to investigate the anti-IDD mechanisms of PT. Moreover, in vivo and in vitro experiment validations including hematoxylin–eosin (HE) and safranine O-green staining, senescence-associated β-galactosidase (SA-β-gal) assay, cell immunofluorescence staining, intracellular ROS measurement and Western blot analysis were performed to verify bioinformatics findings. Results We identified 342 and 872 PT- and IDD-related targets (32 overlapping targets). GO enrichment analysis yielded 450 terms related to oxidative stress and inflammatory response regulation. KEGG analysis identified 48 signaling pathways, 10 of which were significant; the TNF-α signaling pathway had the highest p-value, and prostaglandin G/H synthase 2 (PTGS2), endothelin-1 (EDN1), TNF-α, JUN and FOS were enriched in this pathway. Histopathological results and safranin O/green staining demonstrated that PT attenuated IDD, and SA-β-gal assay showed that PT ameliorated nucleus pulposus cell (NPC) senescence. An ROS probe was adopted to confirm the protective effect of PT against oxidative stress. Western blot analyses confirmed that PT downregulated the protein expression of PTGS2, EDN1, TNF-α, JUN and FOS in the TNF-α signaling pathway as well as cellular senescence marker p16, proinflammatory cytokine interleukin-6 (IL6), while PT upregulated the expression of NPC-specific markers including COL2A1 and ACAN in a concentration-dependent manner. Conclusions To the best of our knowledge, this study is the first to report that PT alleviates IDD by downregulating the protein expression of PTGS2, EDN1, TNF-α, JUN and FOS in the TNF-α signaling pathway and upregulating that of COL2A1 and ACAN, thus suppressing inflammatory responses and oxidative stress in NPCs.